Immunohistochemical evaluation of cell proliferation and apoptosis markers in ovaries and uterus of tamoxifen-treated rats. Issue 1 (1st January 2008) - Cirpan, T.; Terek, M. C.; Ulukus, M.; Ulukus, E. C.; Akman, L.; Kanit, L.
Abstract : The aim of the study was to evaluate the immunohistochemical expression of cell proliferation and apoptosis markers in the ovaries and uterus of tamoxifen-treated rats. Twelve rats (150–200 g) were divided into two equal groups. The study group received daily intraperitoneal injections of tamoxifen dissolved in 5% dimethyl sulfoxide ( n = 6). The control group received only the vehicle ( n = 6). The rats were sacrificed at the 20th day of injection and were perfused. The ovaries and uterus of the rats were extracted. The sections were immunohistochemically stained with cell proliferation marker Ki-67 and the apoptosis markers PTEN and CD95. The expressions of the markers were quantified by a semiquantitative H-score method in myometrium, endometrial glands, ovarian surface epithelium, ovarian follicles, corpus luteum, and ovarian stroma separately. The mean H-scores of CD95 and PTEN obtained from myometrium, glandular endometrium, ovarian surface epithelium, ovarian follicles, corpus luteum, and ovarian stroma did not show significant difference between the study and the control groups. Proliferative index (Ki-67) of endometrial glands was significantly higher in the study group than in the control group ( P < 0.05). In addition, proliferative index (Ki-67) of corpus luteum was significantly higher in the study group than in the control group ( P < 0.05). Tamoxifen treatment has a potential to stimulate the cell proliferation of endometrial glands and corpus luteum in tamoxifen-treated rats. Apoptosis markers of PTEN and CD95 did not demonstrate significant difference after the tamoxifen treatment.